Gambaran sikap dan gaya hidup sehat masyarakat Indonesia selama pandemi Covid-19 - Taufiq Firdaus Alghifari Atmadja; Andi Eka Yunianto; Emy Yuliantini; Miratul Haya; Ahmad Faridi; Suryana Suryana (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2020)
In March 2020 the public was shocked by the Covid-19 pandemic which began to spread to Indonesian territory. Covid-19 is caused by severe acute respiratory syndrome Coronavirus 2 (Severe Acute Respiratory Syndrome Coronavirus 2 or SARS-CoV-2) and is an infectious disease. Naturally, Covid-19 pandemic affects people's attitudes to adopt a healthier lifestyle. The research objective was to analyze the description of the attitudes and lifestyles of the Indonesian people during the Covid-19 pandemic. This study used a cross-sectional design with random sampling and data collection was done by distributing online questionnaires via WhatsApp. Data analysis used the univariate test with the number of respondents as many as 6.557 people. The results showed that the attitudes of respondents regarding the Covid-19 pandemic obtained 6.136 respondents agreed that Covid-19 could be controlled, 6.038 respondents agreed that Indonesia would be free from the coronavirus and 6.489 respondents agreed that consumption of balanced nutritional food, maintaining distance and washing hands properly can prevent the transmission of Covid-19. A total of 3,861 respondents did physical activity less than 3 times a week, 6.234 respondents processed their food, 3,309 respondents sometimes consumed fruit and vegetables, 5.111 respondents always washed their hands using running water and soap, 3.576 respondents sometimes sunbathing above 9 o'clock. Overall, the respondents' behavior towards pandemic conditions shows an optimistic attitude that they can avoid Covid-19 by making healthier lifestyle changes.